Efek Keputusan Pendanaan terhadap Nilai Perusahaan: GCG sebagai Variabel Moderasi - Lorensia Fidelia Charita; Apriani Dorkas Rambu Atahau; Samuel Martono (Postgraduate Program Merdeka University, 2021)
This study aims to examine the effect of funding decisions on firm value with Good Corporate Governance as a moderating variable. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Using purposive sampling method with a total sample of 160 companiesduring 2016-2019 periods, the data were analyzed with panel data regression. The findings shows that the funding decision negatively affect the firm value, while GCG failed to moderate the effect of funding decision on firmvalue. It implies that firms need to optimize their level of debt to boost the value of the firms.Investors see that the company has not been able to manage debt to improve the firm's performance properly. So that an increase in debt will tend to reduce the value of the firms.DOI: https://doi.org/10.26905/afr.v4i2.6137